As a Consequences of the Law of Unilaterally Closing Road Access for Public Road Interests (Case Study of Register Number 92 / Pdt.G / 2021 / PN. Sim) - Alberto Paskah Tarigan; Hisar Siregar; Roida Nababan (Journal of Law, Politic and Humanities, 2025)
This research examines the legal consequences of unilaterally closing public road access based on case study Number 92/Pdt.G/2021/PN. Sim. This closure gave rise to legal and social disputes in society. With a normative juridical approach, this research analyzes legal bases such as the UUPA, Civil Code, and Road Law. The research results show that the act of closing road access without a valid legal basis violates the principle of the social function of land rights (Article 6 UUPA) and can be categorized as an unlawful act (Article 1365 of the Civil Code). The main obstacles in resolving disputes are the defendant's non-compliance with legal decisions and weak enforcement of regulations. Therefore, it is necessary to strengthen regulations regarding road access, increase the government's role in mediating land disputes, as well as legal education for the community to prevent similar conflicts in the future.